Performance Assessment Task dalam pembelajaran Matematika : Analisis student performance - Supriati, Nani Supriati; Putri Mubarika, Melinda (Pasundan Journal of Mathematics Education : Jurnal Pendidikan Matematika, 2025)
This study investigates the impact of performance assessment tasks on mathematics learning outcomes, with particular attention to potential differences based on student gender. Employing a quasi-experimental design with non-equivalent control groups, 80 vocational pharmacy students in Bandung were divided evenly into experimental and control groups. The study aimed to evaluate whether performance assessment tasks improve mathematical knowledge, problem-solving strategies, communication skills, and attitudes toward mathematics, and whether effectiveness differs by gender. Data were collected through tests and questionnaires, then analyzed using descriptive and inferential statistics. Results showed that while the experimental group's scores improved compared to the control group, the difference was not statistically significant for either male or female students. The most notable finding was a strong association between attitudes toward mathematics and learning outcomes, particularly among female students (r=0.878, p<0.001). These results suggest that performance assessment tasks show promise as a learning strategy, though their effectiveness requires further validation. The findings highlight the critical importance of fostering positive student attitudes in mathematics instruction to enhance performance. Study limitations include the small sample size and short intervention period. The study underscores the need to design learning approaches that balance cognitive and affective aspects, particularly in vocational education contexts.